2005
DOI: 10.1152/ajpgi.00121.2005
|View full text |Cite
|
Sign up to set email alerts
|

Insulin secretion-independent effects of GLP-1 on canine liver glucose metabolism do not involve portal vein GLP-1 receptors

Abstract: Whether glucagon-like peptide (GLP)-1 requires the hepatic portal vein to elicit its insulin secretion-independent effects on glucose disposal in vivo was assessed in conscious dogs using tracer and arteriovenous difference techniques. In study 1, six conscious overnight-fasted dogs underwent oral glucose tolerance testing (OGTT) to determine target GLP-1 concentrations during clamp studies. Peak arterial and portal values during OGTT ranged from 23 to 65 pM and from 46 to 113 pM, respectively. In study 2, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 51 publications
(73 reference statements)
4
44
2
Order By: Relevance
“…This was further confirmed in dogs (34) but remains contradictory (35,36), depending on the model studied. Balkan et al (37) showed that portal GLP-1 increased insulin secretion through a mechanism that requires the autonomic nervous system to transmit the glucose signal to the pancreas.…”
Section: Glp-1r-dependent Actions Of Oligofructosementioning
confidence: 68%
“…This was further confirmed in dogs (34) but remains contradictory (35,36), depending on the model studied. Balkan et al (37) showed that portal GLP-1 increased insulin secretion through a mechanism that requires the autonomic nervous system to transmit the glucose signal to the pancreas.…”
Section: Glp-1r-dependent Actions Of Oligofructosementioning
confidence: 68%
“…Although there is little meaningful evidence indicating expression of the GLP-1R in the liver (24,31), there are several reports of GLP-1-mediated regulation of hepatic glucose production in a manner separate from its ability to suppress glucagon release and, intriguingly, independent of insulin (32)(33)(34)(35). We therefore measured EGP rates to investigate whether a GLP-1R-dependent mechanism accounts for regulating glycemia in Gcgr 2/2 animals.…”
Section: Glp-1r Ablation Increases Egp In Insulinopenic Gcgr-null Micementioning
confidence: 99%
“…First, GLP1 acts on the liver to decrease endogenous glucose output [18]. As GLP1 is secreted by the L cells of the gut, the postprandial portal vein concentrations of GLP1 are twice that of the systemic circulation [19]. Thus, GLP1 secretion may indeed be reduced in carriers of the T allele at rs7903146, but this is not detectable at the levels measurable in the systemic circulation.…”
Section: Tcf7l2 and Insulin Actionmentioning
confidence: 99%